A paper-based device of a specially designed soft layered polymer composite for measurement of weak friction force. Issue 4 (22nd November 2019) - Watanabe, Kei; Imai, Hiroaki; Oaki, Yuya
Abstract : A paper-based device of a specially designed soft layered composite consisting of polydiacetylene enables measurement of friction force with a gradual color change from blue to red in response to the strength and number of the applied friction force. Abstract : Measurement of friction force is important for safety, security, and health. Excessive friction force causes degradation of materials and biological bodies. For example, tooth enamel and gums are damaged by strong toothbrushing force. However, friction force is not easily measured by conventional materials and devices. Here, we proposed design strategies of a paper-based device for measurement of friction force. Toothbrushing force, a model of weak friction force, is the measurement target in the present work. Soft layered composites of polydiacetylene (PDA) and interlayer guest macromolecules were designed and synthesized to achieve a visible color change in response to weak friction force. A data-scientific approach assisted in the selection of the interlayer guest molecule to control the stimuli responsivity of the layered PDA. The guest polyethyleneimine (PEI) formed soft layered composites exhibiting a color change in response to weak friction force. The paper-based device of the layered PDA/PEI composite showed a gradual color change from blue to red in response to the strength and number of the applied friction force. As a model case, toothbrushing force was measured using the paper-based device. The present work shows new design strategies of molecules and materials toward measurement of a wide variety of friction forces.